2021
DOI: 10.3390/foods10123122
|View full text |Cite
|
Sign up to set email alerts
|

Food Neophobia, Odor and Taste Sensitivity, and Overall Flavor Perception in Food

Abstract: Smell, which allows us to gather information about the hedonic value of an odor, is affected by many factors. This study aimed to assess the relationship among individual factors, odor sensitivity, and enjoyment, and to evaluate how overall flavor perception and liking in actual food samples are affected by odor sensitivity. A total of 749 subjects, from four different Italian regions, participated in the study. The olfactory capabilities test on four odors (anise, banana, mint, and pine), as well as PROP (6-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 130 publications
1
5
0
Order By: Relevance
“…However, when the rejected vegetables are commonly consumed in the region where the adolescents lived [47], such as the consumption of asparagus in the present study among adolescents from Castilla-La Mancha, these vegetables were accepted due to the high familiarity of the adolescents with this food [17,40], which is in accordance with the well-assumed knowledge that food neophobia is negatively associated with the acceptance not only of new or unfamiliar foods but also of familiar foods [48]. Therefore, the treatment of food neophobia should include familiarization with new foods and their appearance, taste, texture, and systematic introduction [8,41].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, when the rejected vegetables are commonly consumed in the region where the adolescents lived [47], such as the consumption of asparagus in the present study among adolescents from Castilla-La Mancha, these vegetables were accepted due to the high familiarity of the adolescents with this food [17,40], which is in accordance with the well-assumed knowledge that food neophobia is negatively associated with the acceptance not only of new or unfamiliar foods but also of familiar foods [48]. Therefore, the treatment of food neophobia should include familiarization with new foods and their appearance, taste, texture, and systematic introduction [8,41].…”
Section: Discussionsupporting
confidence: 85%
“…It may be due to a combination of biological, psychological, and environmental factors. These include individual, cultural and religious predispositions, preference or rejection of a taste (i.e., salt, sweet, or bitter) as well as overall flavor perception, where taste and odor are combined, familiarity with a taste or a smell, texture (crunchy when raw, soft after excessive cooking Foods 2023, 12, 3717 2 of 16 or fibrous), the moment and method of introducing new products, exposure to foods at an early age, ignorance or negative experience when trying these foods, either due to an inadequate diet or cooking or due to a family environment not conducive to a particular food's consumption, parents' attitude towards foods, and physiological conditions (health status) or genetic factors which are still being studied [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the food characteristics, such as its composition and nature, the deformation rate in the mouth can influence texture perception (Mathoniere et al, 2000). Odors can be evaluated based on their hedonic value by our sense of smell (Puleo et al, 2021). Humans share a sense of smell with many animal species that was crucial to their survival and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to added spices, herbs, and rapeseed oil during preparation [13]. Puleo and others [110] reported that the aroma of foods plays a pivotal role in the perception and liking of food products, especially in new product development. On the other hand, unlike a pleasing aroma, an offensive smell of foods is one of the primordial senses to avoid potential food hazards and contributes to the evolutionary function of disgust as a disease avoidance mechanism [111,112].…”
Section: Sensory Propertiesmentioning
confidence: 99%